2016
DOI: 10.1021/acs.jafc.6b00503
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Characterization of Carotenoid-Oxygen Copolymers in Fruits and Vegetables with Potential Health Benefits

Abstract: We reported previously that the spontaneous oxidation of β-carotene and other carotenoids proceeds predominantly by formation of carotenoid-oxygen copolymers and that β-carotene copolymers exhibit immunological activity, including priming innate immune function and limiting inflammatory processes. Oxidative loss of carotenoids in fruits and vegetables occurs during processing. Here we report evidence for the occurrence of associated analogous copolymer compounds. Geronic acid, an indirect, low molecular weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(58 citation statements)
references
References 27 publications
2
56
0
Order By: Relevance
“…These results were further confirmed using calli from one ZmPSY1 -expressing line, which over-accumulates β-carotene just like AtPSY -overexpressing lines [ 60 ] and showed similar increases in apocarotenoid levels ( Fig 5 ). Moreover, we determined about 50-fold increased amounts of geronic acid, which is liberated from carotenoid-oxygen copolymers and corroborates the non-enzymatic degradation of β-carotene in calli ( S5 Fig ) [ 38 , 63 ].…”
Section: Resultssupporting
confidence: 77%
“…These results were further confirmed using calli from one ZmPSY1 -expressing line, which over-accumulates β-carotene just like AtPSY -overexpressing lines [ 60 ] and showed similar increases in apocarotenoid levels ( Fig 5 ). Moreover, we determined about 50-fold increased amounts of geronic acid, which is liberated from carotenoid-oxygen copolymers and corroborates the non-enzymatic degradation of β-carotene in calli ( S5 Fig ) [ 38 , 63 ].…”
Section: Resultssupporting
confidence: 77%
“…Geronic acid is an indirect, low molecular weight marker indicating the presence of OxBC. The geronic acid method is described in Burton et al (12) , and the multiplying factor is 50 in going from the geronic acid measurement to the calculated OxBC (12) .…”
Section: Oxidised β-Carotene Content In Milkmentioning
confidence: 99%
“…Taken together, the presence and natural occurrence of the copolymers, their immunological activity and their effect on animal health have led to the suggestion that these compounds may be the actual source of the vitamin A-independent effects of β-carotene (6)(7)(8)11,12) .…”
mentioning
confidence: 99%
“…In the trials reported here, the source of the β-carotene copolymers is a commercial product manufactured by a highly reproducible process under stringent quality control standards. However, the copolymers have also been shown to exist naturally at varying levels in various food and feedstuffs (Burton et al, 2016; Schaub et al, 2017). The presence of naturally occurring copolymers may provide an explanation, at least in part, for the health and productivity benefits associated with the use of certain traditional forages.…”
Section: Discussionmentioning
confidence: 99%
“…For example, alfalfa, a forage rich in β-carotene, has been proposed to contain unidentified growth factors that benefit the growth and reproductive performance of various species (Scott et al, 1953; Lakhanpal et al, 1966; Hertrampf and Piedad-Pascual, 2000). The mechanisms of action of the so-called unidentified growth factors remains largely unknown; however the presence of naturally occurring copolymers arising from oxidation of β-carotene when alfalfa is dried (Burton et al, 2016) represents one possible growth factor.…”
Section: Discussionmentioning
confidence: 99%